Направление сил, действующих на листовой ферромагнетик, в зависимости от временных характеристик при МИОМ - Батыгин, Юрий Викторович; Гнатов, Андрей Викторович; Щиголева, Светлана Александровна (НТУ "ХПИ", 2011)
В работе обоснован физический механизм силового воздействия импульсных магнитных полей на тонкостенные листовые заготовки из ферромагнитных проводников. Показано, что при низких рабочих частотах превалируют силы притяжения, обусловленные магнитными свойствами металла. При повышении частот сверх определенного порогового значения притяжение сменяется отталкиванием, обусловленным влиянием сил Лоренца

In the article, the physical mechanism of pulse magnetic fields force action on thin-wall sheet ferromagnetic conducting plates is theoretically formulated and justified. It is shown that attracting forces caused by magnetic properties of the work object metal prevail at low working frequencies. Increasing frequencies over a specified threshold value results in attraction changing into repulsion caused by prevailing action of Lorenz forces resulted from electrodynamic interaction of external fields with induced eddy currents
Direction of force action on sheet ferromagnetic as function of time characteristics under electromagnetic forming
Keywords: магнитно-импульсные технологии; силы Лоренца; притяжение; магнитное поле; отталкивание; electromagnetic forming; thin-wall ferromagnetic plates; pulse magnetic fields force action; physical mechanism